Effect of irrigation frequency and fungicide spray on yield and disease infection of onion (Bangladesh Journal of Agricultural Research, 2009)
A two-year field experiment was conducted at Regional Agricultural Research Station, Jessore during the rabi seasons of 2002-2003 and 2003-2004 to find out the level of disease incidence under different levels of irrigation and fungicide spray on the bulb yield of onion. Four irrigation levels: no irrigation (I1), irrigation at 10 days interval (I2), 20 days interval (I3), and 30 days interval (14) with 4 spray schedules: no spray (F1), one spray at 40 days after transplanting (DAT) (F2), two sprays each at 40 and 55 DAT (F3) and three sprays each at 40, 55, and 70 DAT (F4) were used. Yield and yield attributes varied significantly (p = 0.05) between sprayed and unsprayed, and irrigated and non-irrigated treatments, respectively. Higher yields were obtained with the higher frequencies of irrigation and spray. Application of fungicide reduced the disease severity significantly, while irrigation had no significant effect on disease infection. But there was a decreasing trend of the disease severity with increasing irrigation frequency. The highest bulb yield of onion (12.45 t/ha) was obtained with a total water use of 245 mm in six applications including an effective rainfall of 16 mm and three sprays. The disease severity between sprayed and unsprayed plots ranged from 1.33 to 3.16 for I1, 1.08 to 2.33 for I2 1.16 to 2.83 for I3, and 1.16 to 3.00 for I4, respectively. Key Words: Onion, disease incidence, irrigation, water use efficiency. DOI: 10.3329/bjar.v34i3.3967 Bangladesh J. Agril. Res. 34(3) : 417-424, September 2009